Pengaruh Buka-Tutup Kandang terhadap Kenyamanan dan Kinerja Produksi Sapi Peranakan Ongole (The Effects of Opening and Closing of House on the Ongole Crossbred Cattle’s Comfort and Performances) - Panjono (Panjono); Endang Baliarti (Buletin Peternakan, 2009)
This experiment was conducted to observe the effects of opening and closing of house on the Ongole Crossbred cattle’s comfort and performances. Nine bulls were divided into three groups of housing. The first group was taken care in the house which was opened in the noon and closed in the night (open-closed house), the second was in the closed house, and the third was in the opened house. The experiment was held for 90 days. The data collected were room condition (wind speed, temperature and humidity), physiological conditions, behaviors, feed and water intake, average daily gain and feed conversion. The data were analyzed by analysis of variance for completely randomized design. The analysis was continued by least significant difference test if there were differences. The result showed that wind’s speed in the open-closed house was significantly higher (P<0.05) than that in the closed house in the noon and significantly lower (P<0.05) than that in the opened house in the night. There was no significantly difference on the room’s temperature among three types of house. Room’s humidity in the open-closed housed was significantly lower (P<0.05) than that in the closed house in the daytime and significantly higher (P<0.05) than that in the opened house in the nighttime. There were no significant difference on the cattle’s physiological conditions, behaviors, physiological conditions, behaviors, feed and water intake, average daily gain and feed conversion among three groups. It wasconcluded that opening in the daytime and closing in the nighttime of house had no effect on the Ongole Cross Breed cattle’s comfort and performances.(Key words: Open-closed house, Comfort, Performance, Ongole crossbred cattle)